Nasolacrimal anatomy and haplorhine origins. Issue 114 (January 2018) - Rossie, James B.; Smith, Timothy D.; Beard, K. Christopher; Godinot, Marc; Rowe, Timothy B.
Abstract: Computed tomography X-ray imaging of the internal face in well-preserved primate fossil crania permits reconstruction of the nature of their nasal anatomy, including some soft-tissue features. These features are diagnostic of the primate suborder Haplorhini, and allow reevaluation of the phylogenetic status of several purported early members of the group. Here we examine the nasolacrimal morphology of a broad sample of extant primates, as well as a number of Paleogene fossils. The extant sample confirms the distinctiveness of the two suborders. Of the fossils studied, only Shoshonius cooperi from the late-early Eocene exhibits evidence of a haplorhine nose. This suggests that the haplorhine oronasal complex may have evolved before the postorbital septum, and strengthens the claim that Shoshonius is a close relative of tarsiers and anthropoids. These results indicate that Omomyiformes is not a monophyletic group, and that few of its members possessed the derived oronasal morphology that characterizes crown haplorhines.